The Pengaruh Lingkungan Kerja Terhadap Kepuasan Kerja Guru di SMK Negeri Berbasis Manajemen Kota Padang - Juwita, Rahma; Marsidin, Sufyarma (Journal of Practice Learning and Educational Development, 2023)
This study aims to get an overview of the influence of the work environment on job satisfaction as well as an overview of the conditions of the work environment and job satisfaction in Management-Based Public Vocational Schools in Padang City. The type of research used is causal associative research with a quantitative approach. The population in this study were all teachers at SMKN 2 and 3 Padang, namely 205 teachers, and the sample was 51 teachers (SMKN 2) and 52 teachers (SMKN 3) using the probability sampling method. The instrument in this study used a Likert scale questionnaire with its validity and reliability tested. The data analysis used is descriptive statistical analysis method. The results of this study indicate that the level of achievement of the work environment at SMKN 2 is 74% "high enough" and SMKN 3 is 80% "high", the level of achievement of job satisfaction at SMKN 2 is 77% "quite high" and SMKN 3 is 83%. "high", and there is a positive influence between the work environment on job satisfaction at SMKN 2 and SMKN 3 Padang, namely 37.7% and 94.1%, which has a significance level of 0.001.